Characterization of shock waves in power ultrasound. (22nd March 2021) - Khavari, Mohammad; Priyadarshi, Abhinav; Hurrell, Andrew; Pericleous, Koulis; Eskin, Dmitry; Tzanakis, Iakovos
Abstract: Abstract : The application of cavitation-induced shock waves generated at low driving frequencies, known as power ultrasound, is essential for a wide range of fields, such as sonochemistry, lithotripsy, nanomaterials, emulsions and casting, to name but a few. In this paper, we present measurements of the shock wave pressures emitted by cavitating bubbles in water, under ultrasonic excitation produced by an immersed probe oscillating at 24 kHz. A broad-spectrum fibre-optic hydrophone calibrated in the range of 1–30 MHz was used for this purpose. Spectral analysis of the data reveals a consistent resonance peak at a very narrow range of frequencies (3.27–3.43 MHz). Results were confirmed using real-time analysis of high-speed recordings. By eliminating other possible sources, we propose that this new peak might be associated with shock wave emissions from collapsing bubbles. Spatial maps obtained by collating individual shock wave pressures highlight the effect of pressure shielding with increasing input power, attributed to a cloud of bubbles surrounding the probe. This work contributes towards the elucidation of the key properties of cavitation-driven shock waves and the underlying mechanisms, essential in controlling the effectiveness of the external processing conditions on various physical, chemical and biological systems.